2020
DOI: 10.3389/fnagi.2020.524369
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Aging and Cellular Stress Contributes to Pathogenesis in Mouse and Human Huntington Disease Neurons

Abstract: Huntington disease (HD) is a fatal, inherited neurodegenerative disorder caused by a mutation in the huntingtin (HTT) gene. While mutant HTT is present ubiquitously throughout life, HD onset typically occurs in mid-life. Oxidative damage accumulates in the aging brain and is a feature of HD. We sought to interrogate the roles and interaction of age and oxidative stress in HD using primary Hu97/18 mouse neurons, neurons differentiated from HD patient induced pluripotent stem cells (iPSCs), and the brains of HD … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 93 publications
(115 reference statements)
0
19
0
Order By: Relevance
“…Therefore, metabolic manipulations have also been considered as a possible therapeutic tool for several neurodegenerative diseases, including HD ( Walker and Raymond, 2004 ; Duan et al., 2003 ; Procaccini et al., 2016 ). Interestingly, the IKK-β pathway in the hypothalamus has also been shown to be a key for the advancement of aging in mice ( Zhang et al., 2013 ) and aging is thought to be involved in HD pathogenesis ( Machiela et al., 2020 ; Machiela and Southwell, 2020 ). Given that the wild-type HTT also has a role in regulating metabolism, as it has been shown by body weight gain phenotype in YAC18 mice ( Pouladi et al., 2010 ) and by using hypothalamic expression of HTT fragments with 18Q in mice ( Soylu-Kucharz et al., 2015 ; Baldo et al., 2013 ), the IKK-β pathway has the potential to induce accelerated aging in HD by linking HTT clearance, metabolism alterations, and aging processes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, metabolic manipulations have also been considered as a possible therapeutic tool for several neurodegenerative diseases, including HD ( Walker and Raymond, 2004 ; Duan et al., 2003 ; Procaccini et al., 2016 ). Interestingly, the IKK-β pathway in the hypothalamus has also been shown to be a key for the advancement of aging in mice ( Zhang et al., 2013 ) and aging is thought to be involved in HD pathogenesis ( Machiela et al., 2020 ; Machiela and Southwell, 2020 ). Given that the wild-type HTT also has a role in regulating metabolism, as it has been shown by body weight gain phenotype in YAC18 mice ( Pouladi et al., 2010 ) and by using hypothalamic expression of HTT fragments with 18Q in mice ( Soylu-Kucharz et al., 2015 ; Baldo et al., 2013 ), the IKK-β pathway has the potential to induce accelerated aging in HD by linking HTT clearance, metabolism alterations, and aging processes.…”
Section: Discussionmentioning
confidence: 99%
“…In response to damage from oxidative stress, HTT localizes to the site of DNA damage and recruits DNA repair proteins [ 71 ]. Accumulation of mtHTT impairs this stress response and makes neurons more sensitive to ROS [ 72 ]. The combined presence of mtHTT and endotoxins causes microglia to release more inflammatory cytokines [ 73 ].…”
Section: Selectivitymentioning
confidence: 99%
“…Similarly, while artificial aging using progerin has been considered as an alternative method of encouraging age-related pathologies in iPSC models of neurodegenerative disorders [ 22 ], the physiological relevance of this technique is questionable [ 100 ]. Machiela et al demonstrated that adeno-associated virus (AAV) transduction of progerin in iPSC-derived NPCs resulted in increased damage in differentiated HD cells but not controls, although both the differentiated control and HD cells exhibited reduced dendritic lengths and similar caspase activation when transduced with progerin as iPSC-derived NPCs [ 31 ]. As two of the three HD iPSC lines investigated by Machiela et al were from juvenile cases of HD, the specificity of artificially induced aging to model the changes that occur before adult-onset HD are called into question.…”
Section: Pluripotent Stem Cell Models Of Huntington’s Diseasementioning
confidence: 99%